The Impact of Auditor’s Industrial Specialization on Detecting Financial Statements Fraud for Listed Firm in Saudi Stock Exchange - Alsulami, Tawfeeq Aide; Zaytoun, Mohamed Khamis (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aims to examine the relationship between Auditor’s Industrial Specialization and fraud detection in financial statements. The research utilizes a sample of non-financial companies listed on the Saudi Stock Exchange during the period from 2018 to 2023. The findings indicate that: (1) the industry-specialized auditor (measured by the number of clients) does not have an additional ability to detect fraud in the financial statements of companies listed in the Saudi Stock Exchange compared to non-industry-specialized auditors. 2) the industry-specialized auditor (measured by the size of revenues) has an additional ability to detect fraud in the financial statements of companies listed in the Saudi Stock Exchange compared to non-industry-specialized auditors. 3) The industry-specialized auditor (measured by the size of assets) has an additional ability to detect fraud in the financial statements of companies listed in the Saudi Stock Exchange compared to non-industry-specialized auditors. The study recommended that companies and audit committees should take into account the industry specialization of the auditor when selecting him to ensure the efficiency and quality of the audit process. It also recommended that audit firms should take into account fraud schemes in the financial statements when audit procedures planning, and when verifying the items of the financial statements, which is reflected in the quality of the professional services they provide, and thus the community’s confidence in their role in achieving the efficiency of the capital market.